PENGARUH PEMBELAJARAN KEWIRAUSAHAAN, EKSPEKTASI PENDAPATAN, DAN LINGKUNGAN SEKOLAH TERHADAP MINAT BERWIRAUSAHA SISWA JURUSAN BISNIS DIGITAL SMK LABSCHOOL UNESA 1 SURABAYA - Intan Permata Sari; Putri Hestiningrum (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
A person's interest in entrepreneurship, including students, is not an innate trait. Instead, this interest is shaped by various factors that influence interest in the soul, namely internal and external factors. Internal factors that have an important role in fostering entrepreneurial interest are learning or knowledge about entrepreneurship. External factors that contribute to fostering entrepreneurial interest are income expectations and the school environment. This study aims to determine the effect of entrepreneurship learning, income expectations, and the school environment on the entrepreneurial interest of students majoring in Digital Business at SMK Labschool Unesa 1 Surabaya. This study uses a quantitative approach with a causal associative method. The study population was all students majoring in Digital Business with a total of 82 students selected using a saturated sampling technique. The instrument used was an online questionnaire via Gfrom. The results of the study indicate that entrepreneurship learning, income expectations, and the school environment influence students' entrepreneurial interest, both partially and simultaneously.